2014
DOI: 10.1021/ef501546e
|View full text |Cite
|
Sign up to set email alerts
|

Process for CO2 Capture Using Ionic Liquid That Exhibits Phase Change

Abstract: A novel process for capturing carbon dioxide from the flue gas of a coal-fired power plant has been shown to reduce parasitic power consumption substantially. The process employs an ionic liquid created at the University of Notre Dame that has a high capacity for absorbing CO 2 by chemical reaction. A distinguishing property of this ionic liquid is that it changes phase from solid to liquid upon reaction with CO 2 . The process uses heat generated by this phase transition to lower parasitic power consumption. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Thus, it was concluded that the PCILs were more energy‐efficient candidates than the aqueous amine solutions. Among the studied PCILs, [P 2222 ][BnIm] was the most promising candidate for CO 2 capture …”
Section: Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was concluded that the PCILs were more energy‐efficient candidates than the aqueous amine solutions. Among the studied PCILs, [P 2222 ][BnIm] was the most promising candidate for CO 2 capture …”
Section: Ionic Liquidsmentioning
confidence: 99%
“…Amongt he studied PCILs,[ P 2222 ][BnIm] was the most promising candidate for CO 2 capture. [113,115] Seo et al also, synthesized af amily of ILs containing the alkylphosphonium cation with AHA-based anions( e.g.,p yrrolide, pyrazolide, triazolide, imidazolide, and indazolide). [114] The results revealed that the cations had only am inor effect on absorption; they affected the physical properties of AHA ILs, such as viscosity.T he AHA-derivedI Ls remainedl iquid under ambient conditions owing to the presence of bulky and unsymmetrical alkyl chains coupled to the phosphonium groups.…”
Section: Phase-change Ionic Liquidsmentioning
confidence: 99%
“…Eisinger and Keller conducted a similar study for ILs that undergo a liquid-solid phase change, however their economic assessment relies on vendor quotes. 26 Zhai 30 and de Riva for selected…”
Section: Introductionmentioning
confidence: 99%
“…−52 kJ mol −1 ) and noted for significantly reducing of the overall heat of adsorption . A process design taking advantage of the lower overall heat of adsorption showed 55 % energy savings compared to standard monoethanolamine (MEA) scrubbing technology …”
Section: Figurementioning
confidence: 99%